The Influence of Digital Influencers on Linguistic Evolution in the Javanese Language - Napitupulu, Merlin Helentina; Situmorang, Sarma (Insan Akademika Publications, 2022)
Language is a dynamic entity that evolves in response to cultural and societal shifts. In the digital age, the emergence of influencers as prominent figures on social media platforms has introduced a new dimension to linguistic evolution. This research delves into the interplay between influencers and the Javanese language, examining linguistic innovations, perceived influence, demographic variations, influencer intentions, and ethical considerations. The findings reveal that influencers wield substantial influence, introducing neologisms, unique communication styles, and shifts in syntax within the Javanese language. They play a pivotal role in shaping cultural norms and values within the Javanese-speaking community. However, linguistic evolution brings about consequences and challenges, including dialectal variations, generational divides, and concerns about authenticity and language preservation. To navigate this linguistic landscape, we propose practical recommendations for linguistic education, responsible language promotion, digital preservation, language policy support, and cross-generational engagement. The coexistence of language preservation and evolution underscores the dynamic nature of the Javanese language and emphasizes the need for collaborative efforts to ensure its enduring vitality in the digital era